Familial neonatal seizures in 36 families: Clinical and genetic features correlate with outcome. (15th May 2015) - Grinton, Bronwyn E.; Heron, Sarah E.; Pelekanos, James T.; Zuberi, Sameer M.; Kivity, Sara; Afawi, Zaid; Williams, Tristiana C.; Casalaz, Dan M.; Yendle, Simone; Linder, Ilan; Lev, Dorit; Lerman‐Sagie, Tally; et al.
Summary Objective We evaluated seizure outcome in a large cohort of familial neonatal seizures (FNS), and examined phenotypic overlap with different molecular lesions. Methods Detailed clinical data were collected from 36 families comprising two or more individuals with neonatal seizures. The seizure course and occurrence of seizures later in life were analyzed. Families were screened for KCNQ2, KCNQ3, SCN2A, and PRRT2 mutations, and linkage studies were performed in mutation‐negative families to exclude known loci. Results Thirty‐three families fulfilled clinical criteria for benign familial neonatal epilepsy (BFNE); 27 of these families had KCNQ2 mutations, one had a KCNQ3 mutation, and two had SCN2A mutations. Seizures persisting after age 6 months were reported in 31% of individuals with KCNQ2 mutations; later seizures were associated with frequent neonatal seizures. Linkage mapping in two mutation‐negative BFNE families excluded linkage to KCNQ2, KCNQ3, and SCN2A, but linkage to KCNQ2 could not be excluded in the third mutation‐negative BFNE family. The three remaining families did not fulfill criteria of BFNE due to developmental delay or intellectual disability; a molecular lesion was identified in two; the other family remains unsolved. Significance Most families in our cohort of familial neonatal seizures fulfill criteria for BFNE; the molecular cause was identified in 91%. Most had KCNQ2 mutations, but two families had SCN2A mutations, which are normally associated with a mixed picture of neonatal and infantile onset seizures. Seizures later in life are more common in BFNE than previously reported and are associated with a greater number of seizures in the neonatal period. Linkage studies in two families excluded known loci, suggesting a further gene is involved in BFNE.